Hahb-10, a sunflower homeobox-leucine zipper gene, is regulated by light quality and quantity, and promotes early flowering when expressed in Arabidopsis - Rueda, Eva Carolina (2005)
Homeodomain-leucine zipper proteins constitute a family of transcription factors found only in plants. Expression patterns of the sunflower homeobox-leucine zipper gene Hahb-10 (Helianthus annuus homeobox-10), that belongs to the HD-Zip II subfamily, were analysed. Northern blots showed that Hahb-10 is expressed primarily in mature leaves, although expression is clearly detectable in younger leaves and also in stems. Considerably higher expression levels were detected in etiolated seedlings compared with light-grown seedlings. Induction of Hahb-10 expression was observed when seedlings were subjected to treatment with gibberellins. Transgenic Arabidopsis thaliana plants that express Hahb-10 under the 35S cauliflower mosaic virus promoter show special phenotypic characteristics such as darker cotyledons and planar leaves. A reduction in the life cycle of about 25% allowing earlier seed collection was also observed, and this phenomenon is clearly related to a shortened flowering time. When the number of plants per pot increased, the difference in developmental rate between transgenic and non-transformed individuals became larger. After gibberellin treatment, the relative difference in life cycle duration was considerably reduced. Several light-regulated genes have been tested as possible target genes of Hahb-10. One of them, PsbS, shows a different response to illumination conditions in transgenic plants compared with the response in wild-type plants while the other genes behave similarly in both genotypes. We propose that Hahb-10 functions in a signalling cascade(s) that control(s) plant responses to light quality and quantity, and may also be involved in gibberellin transduction pathways.